Bilayer graphene with ripples for reverse osmosis desalination. (September 2018) - Shi, Qi; Gao, Haiqi; Zhang, Yadong; Meng, Zhaoshun; Rao, Dewei; Su, Jiaye; Liu, Yuzhen; Wang, Yunhui; Lu, Ruifeng
Abstract: Water desalination is a widely-used strategy to provide fresh water around the world. Herein we report an atomistic simulation study on water desalination in a series of bilayer graphene with different ripples. By carefully analyzing the orientation, density map, and transmembrane velocity of water molecules, it is found that the size of interlayer space formed by ripples affects the water transport. With some appropriate ripples, water molecules pass through bilayer graphene with two or three ordered channels during the transmembrane process. For small and middle ripples, water molecules enter the transport channel with an entrance-angle and need to change their orientation to exit the graphene layers. One of the bilayer graphene (BGR) membranes with ripples, BGR-1.6, exhibits the best performance with water permeance of 1020 kg m h −1  bar −1 and 98.1% salt rejection, which is three orders higher than commercial seawater reverse osmosis membranes. This theoretical study provides microscopic insights into the role of ripples in governing membrane properties and desalination performance. Graphical abstract: Image 1